Military Resisters, War Resistance, and the Ethics of Exposure and Disclosure. (October 2014) - Weedon, Gavin
Traitorous cowards or courageous heroes? Military resisters elicit fervent responses not simply because they polarize perspectives on war, nation, and citizenship, but because they encounter and embody a moral quandary which marks all conflict: The fear of harming another when one's own life, and sense of self, is endangered. With recourse to Judith Butler's meditations on the precarity of life and the finitude of liberal humanist ontologies, this article contemplates the ethical imperative of eschewing both the valorization and demonization of individual resisters who found perpetrating war too much to bear. My focus lies in 21st-century U.S. military resisters who journey to Canada in search of refuge, residency, and "peace of mind." While their experiences are imbued with ethical promise for amplifying oppositional political perspectives on war, this promise is inhibited by the legal and political apparatuses in which they are constituted, through which they are individuated, and to which they remain bound.